Digital Transformation: A Case Study of a Legal Firm in Sri Lanka and Its Impact - Dulanjani Dissanayake; Kajini Pasadika Hapuarachchi Hapuarachchige; Yogesh Jindal (International Journal of Management and Data Analytics)
The legal industry is rapidly transforming, and Goldman Sachs experts estimate that 44% of legal work can be automated, highlighting the legal industry's pivotal role in technological advancement. Presently, there is a critical gap in the operational efficiency of law firms in Sri Lanka compared to those in developed countries. This study is with special reference to D.L&F. De. Saram company’s manual practices, which hinder its operational effectiveness and adaptability in the contemporary legal landscape, where quick and secure access to information is pivotal. We have adopted TAM as the theoretical framework for this research. The proposed comprehensive digital transformation addresses this gap by implementing a cloud-based Customer Relationship Management (CRM) System, integration of Artificial Intelligence (AI) for data handling, Case Analysis and Management Software, Legal Research Software, and enhancement of cyber security measures. Furthermore, the article proposes using advanced video conferencing tools to enhance client communication. These changes aim to bring substantial value to the firm by streamlining and automating routine tasks and securing confidential client data. This transformation is expected to increase operational efficiency, reduce cost, improve client services, and enhance the satisfaction and retention of clients.